Strategies to Introduce Computational Thinking to Children: An Analysis based on Cultural Viewpoint Metaphors - Oliveira, Gabriela Amaral Araujo de; Assunção, Oto Braz; Prates, Raquel Oliveira (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na Educação, 2019)
Computational thinking (CT) is regarded as an essential competence for people living in the 21st century. Hence, several materials for teaching CT have been developed. Although there are studies that classify materials and approaches for teaching CT, an analysis regarding how deeply they present computing concepts to students is still lacking. In this research, we conduct such analysis using an epistemic tool called Cultural Viewpoint Metaphors (CVM). We first analyze existing research on computational thinking teaching. Then, we classify the tools and teaching methods used in those works in light of CVM. We expect our analysis can support educators to select teaching materials for the activities they will conduct and define the order in which they will be applied.